Aspirin is associated with improved 30-day mortality in patients with sepsis-associated liver injury: a retrospective cohort study based on MIMIC IV database - Wang, Jianbao; Hu, Xuemei; Cao, Susu; Zhao, Yiwen; Chen, Mengting; Hua, Tianfeng; Yang, Min (Frontiers in Pharmacology, 2025)
BackgroundSepsis-associated liver injury (SALI) is a common complication in sepsis patients, significantly affecting their prognosis. Previous studies have shown that aspirin can improve the prognosis of septic patients. However, there is currently a lack of clinical evidence supporting the use of aspirin in the treatment of SALI. Therefore, we conducted this study to explore the association between the use of aspirin and the prognosis of patients with SALI.MethodsThe patients in this study were obtained from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database, version 3.0. The primary outcome was 30-day all-cause mortality. Baseline characteristics between the aspirin and non-aspirin groups were balanced using propensity score matching (PSM). The Kaplan-Meier survival curve and Cox regression analysis were used to investigate the association between aspirin use and the prognosis of patients with SALI.ResultsOf 657 SALI patients in this study, 447 (68%) patients had not used aspirin during hospitalization, whereas 210 (32%) had. After PSM, the 30-day mortality was 33.1% in the non-aspirin group and 21% in the aspirin group, indicating a significantly reduced mortality risk in the aspirin group (HR, 0.57; 95% CI, 0.37–0.90; P = 0.016). Similarly, the results of the multivariable Cox regression analysis and inverse probability weighting (IPW) analysis showed that, compared to the non-aspirin group, the aspirin group had a significantly lower 30-day mortality risk (Multivariable Cox regression analysis: HR, 0.69; 95% CI, 0.48–0.99; P = 0.047; IPW: HR, 0.62; 95% CI, 0.43–0.89; P = 0.010).ConclusionAspirin can reduce 30-day mortality in SALI patients, regardless of the dose or timing of administration. However, careful assessment based on individual differences is essential to ensure the safety and effectiveness of aspirin use.